Web based map of central part of University of Technology Malaysia using macromedia dream weaver [electronic resource] - 387148 Fung, Sheaw Tyan (2010)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2010